2015
DOI: 10.1088/0004-637x/806/2/271
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Arrival Time of Coronal Mass Ejections With the Graduated Cylindrical Shell and Drag Force Model

Abstract: Accurately predicting the arrival of coronal mass ejections (CMEs) at the Earth based on remote images is of critical significance in the study of space weather. In this paper, we make a statistical study of 21 Earth directed CMEs, exploring in particular the relationship between CME initial speeds and transit times. The initial speed of a CME is obtained by fitting the CME with the Graduated Cylindrical Shell model and is thus free of projection effects. We then use the drag force model to fit results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 64 publications
3
72
1
Order By: Relevance
“…The dotted line denotes the expected proton temperature from the observed speed and Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA). The GCS model is capable of describing a wide range of quantities including the bulk velocity mass distribution and three-dimensional trajectory of the CME (e.g., Shi et al 2015). Figure 3 shows application of the GCS model to the 16 June 2010 CME event, which is a relatively slow CME occurring with the eruption of a quiescent filament.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dotted line denotes the expected proton temperature from the observed speed and Solar Dynamics Observatory (SDO) Atmospheric Imaging Assembly (AIA). The GCS model is capable of describing a wide range of quantities including the bulk velocity mass distribution and three-dimensional trajectory of the CME (e.g., Shi et al 2015). Figure 3 shows application of the GCS model to the 16 June 2010 CME event, which is a relatively slow CME occurring with the eruption of a quiescent filament.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
“…The model in this case shows evidence for a variety of physical processes we will discuss in following sections, including super-radial expansion and rotation within the first 5 R . In several examples (e.g., Liu et al 2010b;Vourlidas et al 2011;Nieves-Chinchilla et al 2012;Isavnin et al 2014;Shi et al 2015;Schmidt et al 2016), the GCS model has shown how the early 3-D evolution of CMEs can be well described as magnetic flux ropes that are prone to both deflection and rotation.…”
Section: Icmes and Magnetic Cloudsmentioning
confidence: 99%
“…The 12 July 2012 event was also discarded because we could not affirm from the microwave profile at 9 GHz that this was gyrosynchrotron emission. We selected 12 more ICME events to increase our sample: six (between 2011 and 2012) from the ISEST catalogue 4 , one from Table 1 in Shi et al (2015) and five (in the years 2013 and 2014) from Table 1 in Mays et al (2015). In addition, the 20 events listed in Table 1 in Gopalswamy et al (2013) were also considered.…”
Section: Nomentioning
confidence: 99%
“…1 in Gopalswamy et al 2013). The speeds resulting from multi-spacecraft modelling by Möstl et al (2014) or Shi et al (2015) are represented by filled blue circles and triangles, respectively. The comparison between predictions, observations and modelling in Figure 5 reveals a large spread of CME speeds derived from different techniques.…”
Section: Cme Speed Determinationmentioning
confidence: 99%
See 1 more Smart Citation